Characteristics of health impact assessments reported in Australia and New Zealand 2005–2009. (5th September 2013) - Haigh, Fiona; Harris, Elizabeth; Chok, Harrison NG; Baum, Fran; Harris‐Roxas, Ben; Kemp, Lynn; Spickett, Jeff; Keleher, Helen; Morgan, Richard; Harris, Mark; Wendel, Arthur M.; Dannenberg, Andrew L.
Abstract Objective : To describe the use and reporting of Health Impact Assessment (HIA) in Australia and New Zealand between 2005 and 2009. Methods : We identified 115 HIAs undertaken in Australia and New Zealand between 2005 and 2009. We reviewed 55 HIAs meeting the study's inclusion criteria to identify characteristics and appraise the quality of the reports. Results : Of the 55 HIAs, 31 were undertaken in Australia and 24 in New Zealand. The HIAs were undertaken on plans (31), projects (12), programs (6) and policies (6). Compared to Australia, a higher proportion of New Zealand HIAs were on policies and plans and were rapid assessments done voluntarily to support decision‐making. In both countries, most HIAs were on land use planning proposals. Overall, 65% of HIA reports were judged to be adequate. Conclusion : This study is the first attempt to empirically investigate the nature of the broad range of HIAs done in Australia and New Zealand and has highlighted the emergence of HIA as a growing area of public health practice. It identifies areas where current practice could be improved and provides a baseline against which future HIA developments can be assessed. Implications: There is evidence that HIA is becoming a part of public health practice in Australia and New Zealand across a wide range of policies, plans and projects. The assessment of quality of reports allows the development of practical suggestions on ways current practice may be improved. The growth of HIA will depend on ongoing organisation and workforce development in both countries.